The role of interiorized power in sexual repression: a foucauldian reading of Edward Albee's The Zoo story - Shayla, Sadia Afrin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.